Patenting productivity and intellectual property policies at Research I universities: An exploratory comparative study. - Mendoza, Pilar; Berger, Joseph B. (Education Policy Analysis Archives, 2005)
In the 1980s, the US government encouraged the cooperation of industries with universities in order to bridge funding gaps and cope with global competitive markets through legislations that allow universities to start spin-off businesses and to generate profits from patents. At the turn of the century, university partnerships with the private sector have greatly increased through research grants, licensing patents, and in some cases, the formation of new firms'mainly at research universities and in the hard sciences. In response to these entrepreneurial opportunities, university administrators developed intellectual property policies to facilitate the commercialization of research. The purpose of this study is to explore the differences across IP policies among nine research universities as potential sources of influence on faculty engagement in for-profit research ventures according to existing models of faculty role performance and achievement.